A megújuló energia termelés támogatásának intézményi változásai - a Megújuló Energia Támogatási Rendszer bevezetése = Institutional changes in support for renewable energy production - introduction of renewable energy support scheme - Haffner, Tamás (Közép-Európai Közlemények, 2018)
The specific costs of using renewable energy sources are many times higher than the specific costs of using fossil fuels therefore its production needs support. Three types of support can be distinguished: investment supports, the green certificate system within the production subsidies and the feed-in tariff system. The latter support system has been operating in Hungary since 2003. Hungary ensured support for green energy production from renewable energy sources within the framework of Feed-in Tariff Payment Scheme since 2003 then within the framework of Feed-in Tariff Scheme (FiT) since 2007. Many criticisms have been expressed about the operation of FiT, from which the displacing effect arising from the bureaucratic nature of the system shall be emphasised. Renewable Energy Support Scheme (RESS) was introduced in Hungary in 2017. Within the framework of the scheme developed in accordance with the directive of the European Union, support can be ensured only through a tender procedure – except for small power plants. The new scheme has many opportunities however the bureaucratic procedure might even lead to a decrease in number of those intending to enter the system.